Lactobacillus rhamnosus LB1 Alleviates Enterotoxigenic Escherichia coli-Induced Adverse Effects in Piglets by Improving Host Immune Response and Anti-Oxidation Stress and Restoring Intestinal Integrity - Wu, Tao; Shi, Yutao; Zhang, Yanyan; Zhang, Min; Zhang, Lijuan; Ma, Zhipeng; Zhao, Di; Wang, Lei; Yu, Hai; Hou, Yongqing; Gong, Joshua (Frontiers in Cellular and Infection Microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) is a common enteric pathogen that causes diarrhoea in humans and animals. Lactobacillus rhamnosus LB1 (formerly named Lactobacillus zeae LB1) has been shown to reduce ETEC infection to Caenorhabditis elegans and Salmonella burden in pigs. This study was to evaluate the effect of L. rhamnosus LB1 on the gut health of lactating piglets that were challenged with ETEC. Six-four piglets at 7 days of age were equally assigned into 8 groups (8 piglets per group): 1) control group (basal diet, phosphate buffer saline); 2) CT group (basal diet + 40 mg/kg colistin); 3) LL group (basal diet + 1 × 107 CFU/pig/day LB1); 4) HL group (basal diet + 1 × 108 CFU/pig/day LB1); 5) ETEC group: (basal diet + ETEC challenged); 6) CT + ETEC group (basal diet + CT + ETEC); 7) LL + ETEC group (basal diet + 1 × 107 CFU/pig/day LB1 + ETEC); 8) HL + ETEC group (basal diet + 1 × 108 CFU/pig/day LB1 + ETEC). The trial lasted ten days including 3 days of adaptation. Several significant interactions were found on blood parameters, intestinal morphology, gene, and protein expression. ETEC infection disrupted the cell structure and biochemical indicators of blood, undermined the integrity of the intestinal tract, and induced oxidative stress, diarrhoea, intestinal damage, and death of piglets. The supplementation of L. rhamnosus LB1 alleviated ETEC’s adverse effects by reducing pig diarrhoea, oxidative stress, and death, modulating cell structure and biochemical indicators of blood, improving the capacity of immunity and anti-oxidation stress of pigs, and restoring their intestinal integrity. At the molecular level, the beneficial effects of L. rhamnosus LB1 appeared to be mediated by regulating functional related proteins (including HSP70, Caspase-3, NLRP3, AQP3, and AQP4) and genes (including RPL4, IL-8, HP, HSP70, Mx1, Mx2, S100A12, Nrf2, GPX2 and ARG1). These results suggest that dietary supplementation of L. rhamnosus LB1 improved the intestinal functions and health of piglets.